Standardisation of a European measurement method for the determination of anions and cations in PM2.5: results of field trial campaign and determination of measurement uncertainty. Issue 12 (25th November 2016) - Beccaceci, Sonya; Brown, Richard J. C.; Butterfield, David M.; Harris, Peter M.; Otjes, René P.; van Hoek, Caroline; Makkonen, Ulla; Catrambone, Maria; Patier, Rosalía Fernández; Houtzager, Marc M. G.; Putaud, Jean-Philippe
Abstract : The results of field trial campaign to validate the European standard measurement method for anions and cations in ambient particulate matter are presented. Abstract : European Committee for Standardisation (CEN) Technical Committee 264 'Air Quality' has recently produced a standard method for the measurements of anions and cations in PM2.5 within its Working Group 34 in response to the requirements of European Directive 2008/50/EC. It is expected that this method will be used in future by all Member States making measurements of the ionic content of PM2.5 . This paper details the results of a field measurement campaign and the statistical analysis performed to validate this method, assess its uncertainty and define its working range to provide clarity and confidence in the underpinning science for future users of the method. The statistical analysis showed that, except for the lowest range of concentrations, the expanded combined uncertainty is expected to be below 30% at the 95% confidence interval for all ions except Cl − . However, if the analysis is carried out on the lower concentrations found at rural sites the uncertainty can be in excess of 50% for Cl −, Na +, K +, Mg 2+ and Ca 2+ . An estimation of the detection limit for all ions was also calculated and found to be 0.03 μg m −3 or below.